Therapeutic Efficacy of Arnica in Hamsters with Cutaneous Leishmaniasis Caused by Leishmania braziliensis and L. tropica (2022)
ABSTRACT: Leishmaniasis may occur in three different clinical forms, namely, visceral, mucocutaneous and cutaneous, which are caused by different species of trypanosomatid protozoans of the genus Leishmania. Pentavalent antimonials are the leading treatment for cutaneous leishmaniasis despite the hepatic, renal, and cardiac toxicity. In addition, the response of some Leishmania species to pentavalent antimonials is increasingly poorer, and therefore new and more potent therapeutic alternatives are needed. Arnica montana L., Asteraceae, is a traditional medicinal plant of Europe and preparations of its flowers are commonly used externally to treat disorders of the musculoskeletal system as well as superficial inflammatory conditions. Previous studies have shown that Arnica tincture (AT), an ethanolic extract prepared from the flowerheads of Arnica montana as well as isolated Arnica sesquiterpene lactones (STLs) have antileishmanial activity in vitro against L. donovani and L. infantum, as well as in vivo against L. braziliensis. In this work, we studied the in vitro cytotoxicity and antileishmanial activity of AT and STLs against both L. braziliensis and L. tropica. The in vivo therapeutic effect of AT was studied in hamsters with cutaneous Leishmaniasis (CL) caused by experimental infection with L. braziliensis and L. tropica. Furthermore, various semisolid Arnica preparations were also evaluated against L. braziliensis. The STLs and the AT possess a very high in vitro activity against both Leishmania species with median effective concentrations (EC50) ranging from 1.9 to 5.9 µg/mL. The AT was not cytotoxic for human tissue macrophages, skin fibroblasts, and hepatic cells. The therapeutic response of hamsters infected with L. braziliensis to the topical treatment with AT was 87.5% at a dose of 19.2 µg STL/2× day/60 d, 72.7% at doses of 19.2 µg STL/1× d/60 d and 67% at a dose of 38.4 µg STL/2× d/60 d. In turn, the therapeutic response in hamsters infected with L. tropica was 100% when treated at a dose of 19.2 µg STL/2× day/60 d and 71% at a dose of 38.4 µg STL/2× d/60 d. On the other hand, the effectiveness of treatment with glucantime administered intralesionally at a dose of 200 mg/every three days for 30 days was 62.5% for L. braziliensis and 37.5% for L. tropica infection. These results are promising and encourage the implementation of clinical trials with AT in CL patients as a first step to using AT as a drug against CL.